ADSORPTION OF CADMIUM(II) IONS FROM AQUEOUS SOLUTION BY TECTONA GRANDIS L.F. (TEAK LEAVES POWDER) - Karanam Srinivasa Rao; Shashi Anand; Paladugu Venkateswarlu (BioResources, 2010)
Batch adsorption studies were undertaken with the abundantly available waste biosorbent Tectona grandis L.f. leaf powder for removal of cadmium(II) from aqueous solutions. The adsorption experiments were performed under various conditions such as time, temperature, different initial Cd(II) concentrations, pH, adsorbent dosage, and adsorbent particle size. The data showed that in 30 minutes, 1 g of Tectona grandis L.f. could remove 86.73% of cadmium(II) from 50 mL aqueous solution containing 100 mg L-1 of Cd. The isothermal data fitted well to both Langmuir and Freundlich models for Cd(II) adsorption on Tectona grandis L.f. Using the Langmuir model equation, the monolayer sorption capacity of Tectona grandis L.f. was evaluated to be 29.94 mg g-1. The optimum pH value was found to be 5.5. The pseudo-first-order and pseudo-second-order kinetic models were used to describe the kinetic data. The dynamic data fitted well to the pseudo-second-order kinetic model. Cd(II) adsorption was only marginally affected in the temperature range of 30 to 50oC. An SEM of Cd(II) loaded powder showed formation of agglomerates. The FTIR of Cd(II) loaded powder showed negative shift in the wave numbers.